Pest categorisation of Pseudocercospora pini‐densiflorae. (8th November 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: Following a request from the European Commission, the EFSA Plant Health (PLH) Panel performed a pest categorisation of Pseudocercospora pini‐densiflorae, a well‐defined and distinguishable fungal species of the family Mycosphaerellaceae. The regulated harmful organism is the anamorph Cercoseptoria pini‐densiflorae (synonym Cercospora pini‐densiflorae ) with the corresponding teleomorph Mycosphaerella gibsonii. P. pini‐densiflorae causes a needle blight of Pinus spp. also known as Cercospora blight of pines or Cercospora needle blight. P. pini‐densiflorae is reported from sub‐Saharan Africa, Central and South America, Asia and Oceania, but not from the EU. The pathogen is regulated in Council Directive 2000/29/EC (Annex IIAI) as a quarantine organism whose introduction into the EU is banned on plants (other than fruit and seeds) and wood of Pinus . The pest could enter the EU via plants for planting and other means (uncleaned seed, cut branches of pine trees, isolated bark, growing media accompanying plants, and mycorrhizal soil inocula). Hosts are widespread in the EU and favourable climatic conditions are present in Mediterranean countries. Pinus halepensis, Pinus nigra, Pinus pinea, Pinus pinaster and Pinus sylvestris are reported to be highly susceptible to the pathogen. The pest would be able to spread following establishment after introduction in the EU mainly on infected plants for planting. The pest introduction could have impacts in nurseries and young plantations. Cleaning seeds from needles and removing infected seedlings and pine litter from affected nurseries can reduce the risk of establishment in nurseries and of spread from nurseries to forests, especially given the limited scale of splash dispersal. The main knowledge gaps concern (i) the role of means of entry/spread other than plants for planting and (ii) the potential consequences in mature tree plantations and forests. The criteria assessed by the Panel for consideration as potential quarantine pest are met. For regulated non‐quarantine pests, the criterion on the pest presence in the EU is not met.